Pengaruh Metode Pembelajaran Berdiferensiasi dan Profesionalisme Guru Terhadap Perkembangan Kemampuan Literasi Siswa SLB di Kabupaten Banyuasin - Suryani Adawiyah; Dessy Wardiyah; Sri Wahyu Indrawati (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
The purpose of this study is to determine and describe the influence of differentiated learning methods and teacher professionalism on the development of literacy skills of SLB students in Banyuasin Regency. This research was conducted at the Special School (SLB) in Banyuasin Regency consisting of 4 schools, namely, SLBN Banyuasin, SLB Rimba Asam, SLB OPI Jakabaring and SLB Adhyastha. This research is a type of quantitative research. The research design used in this study is a correlational research design. The population and sample in this study amounted to 34 teachers. Data collection techniques using questionnaires, questionnaires and documentation. Data analysis techniques use normality tests, linearity tests, multicollinearity tests, simple correlation analysis, multiple correlation analysis, simple regression analysis, t tests and F tests. The result of this study is that there is an influence of differentiated learning and teacher professionalism on the literacy ability of SLB students in Banyuasin Regency. The figure obtained by the R Square (R2) coefficient of determination is 0.296 which means that the influence of differentiated learning and teacher professionalism is able to contribute to the literacy ability of SLB students in Banyuasin Regency by 29.6%, while the remaining 70.4% is influenced by other factors not mentioned in this study. In conclusion, there is an influence of differentiated learning methods and teacher professionalism on the development of literacy skills of special school students in Banyuasin Regency. Keywords: Differentiated Learning, Literacy Ability, Professionalism of teachers;